2022
DOI: 10.1039/d1ra08447j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid hydrogels derived from renewable resources as a smart stimuli responsive soft material for drug delivery applications

Abstract: The design and synthesis of amphiphilic molecules play a crucial role in fabricating smart functional materials via self-assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Indeed, the significance of soft materials in various sectors further motivated researchers to investigate these fascinating materials. In this context, our research group has reported the design, synthesis, and potential applications of pyrene-based amphiphiles. , In an attempt to understand the bottom-up assembly of DPSC, initially, we have synthesized DPSC from D-sorbitol and pyrene-1-carboxaldehyde using relatively a simple procedure given in Scheme . , In 1 H NMR spectra, the presence of a singlet at δ = 6.45 ppm and a peak at δ = 99 ppm in the 13 C NMR spectrum confirms the formation of acetal in DPSC. After the product formation was confirmed by various spectral techniques, the supramolecular assembly of DPSC is studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the significance of soft materials in various sectors further motivated researchers to investigate these fascinating materials. In this context, our research group has reported the design, synthesis, and potential applications of pyrene-based amphiphiles. , In an attempt to understand the bottom-up assembly of DPSC, initially, we have synthesized DPSC from D-sorbitol and pyrene-1-carboxaldehyde using relatively a simple procedure given in Scheme . , In 1 H NMR spectra, the presence of a singlet at δ = 6.45 ppm and a peak at δ = 99 ppm in the 13 C NMR spectrum confirms the formation of acetal in DPSC. After the product formation was confirmed by various spectral techniques, the supramolecular assembly of DPSC is studied.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, our research group has reported the design, synthesis, and potential applications of pyrene-based amphiphiles. 8 , 58 68 In an attempt to understand the bottom-up assembly of DPSC, initially, we have synthesized DPSC from D-sorbitol and pyrene-1-carboxaldehyde using relatively a simple procedure given in Scheme 1 . 40 , 69 75 In 1 H NMR spectra, the presence of a singlet at δ = 6.45 ppm and a peak at δ = 99 ppm in the 13 C NMR spectrum confirms the formation of acetal in DPSC.…”
Section: Resultsmentioning
confidence: 99%
“…These functionalized gelatin complexes could provide both structural and bioactive functions if incorporated into a bigel [ 103 ]. Using multiple gelators to co-structure the gels can modulate the mechanical properties of the gels and even provide additional release triggers [ 98 , 104 ]. Co-polymer gels (e.g., gelatin–agar-based co-hydrogels) can be achieved by tailoring the composition of bio-compatible gelators [ 54 ].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Because of their broad range of applicational potential, researchers have been studying hydrogels for years. The biomedical and pharmaceutical industries have primarily implemented hydrogels as delivery systems [4,5], scaffolds for cell cultivation [6], and tissue engineering [7]. However, when it comes to the food industry, the implementation of hydrogels is constrained by restrictions on the use of certain ingredients that need to be food-grade, generally recognized as safe (GRAS) by the Food and Drug Administration (FDA) in the USA and included in the EU list of permitted food additives laid down in Regulation EC 1333/2008.…”
Section: Introductionmentioning
confidence: 99%